FAKTOR- FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PENDERITA TB PARU DALAM MINUM OBAT DI WILAYAH KERJA PUSKESMAS GUNDIH KOTA SURABAYA TAHUN 2016 - Desi Lutfianti; AT Diana Nerawati; Ferry Kriswandana (Poltekkes Kemenkes Surabaya, 2017)
ABSTRACTTuberculosis (TB) is an infection caused by Micobacterium tuberculosis bactery which is transmittedthrough the air. Surabaya contributes to pulmonary TB with highest cases and a treatment success rate of78.8% in 2012. Behavioral factors in taking medicine is very influential in the treatment success. This researchaims at determining the factors related to the behavior of pulmonary TB patients in taking medication at Gundihhealth center 2016.This research is crossectional, 37 patient samples are taken by simple random sampling. Data collectionis done by using oral questionnaire and written questionnaire. The data obtained and being analyzed byunivariate and bivariate in form of Chi square test.The study result shows that 78% of respondents behave (knowledge, attitude, action) well, 55% ofrespondents do not have Drug Taking Supervisor and 45% of Drug Taking Supervisor play their role 82% well,then 51% of TB educational media is considered unfavorable, and 87% of respondents have good family support.From these factors, family support is the factor that has significant influence with the respondent's behavior intaking medication (P 0.05).Factors related to the behavior of respondents in taking medication are related to each other so thatpatients can be cured with the results of Acid-Resistant Bacili (-). TB patients are suggested to to improvetheir knowledge. For Drug Taking Supervisor, it is suggested to motivate and remind the patients to takemedication. The society are also suggested to immediately report if there are patients who have majorsymptoms of TB. Health centers is suggested to monitor the condition of patients‟ house. Finally, furtherresearchers are expected to examine deeper the relationship between the presence or absence of the DrugTaking Supervisor with the behavior of patients with pulmonary tuberculosis in taking medicine.Keywords : Behavioral factors, Drug Taking Supervisor, Medicines Availability, Educational Media, FamilySupport